MASALAH SENGKETA CLAIM PULSA DAN CARA PEMBUKTIANNYA - Marten R Robin (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
AbstractDevelopment in all fields and in particular telecommunication everything goes according to the law. Based on Government Regulation No. 24 Year 1991 dated May 1, 1991, the Housing Telecommunications (PERUMTEL) was changed to PT. (Persero) Telecommunications Indonesia. As its realization on September 24, 1991 in the presence of Notary Imas Fatimah, SH established PT (Persero) Telecommunications Indonesia. The changes are not only an impact in the field of management / management, but also bring changes in its status as a legal entity that is of public legal entity into a private legal entity. Although the change of legal status does not change his position as State-Owned Enterprises (SOEs). So that no claim again, should the completion of the peace efforts deed peace each hold the deed and each again have the same legal force as well as the legal powers decided by the district court.